AI and developers: degradation of skills or increased efficiency? - Baklanov, Konstantin; Tadjikhodjaeva, Elvira (MMIT Proceedings, 2025)
The article analyzes the impact of generative artificial intelligence on the professional skills of IT specialists. The risks of loss of routine skills and opportunities to increase productivity are considered. There are differences in the perception of AI between beginners and experienced developers.